The Value of Time - Festjens, Anouk and Janiszewski, Chris (Journal of Consumer Research, 2015)
Abstract Ten studies are used to document that time is valued in accordance with a double-kinked value function. There is a zone of indifference for small time gains (losses), increasing marginal utility (disutility) for moderate time gains (losses), and diminishing marginal utility (disutility) for large time gains (losses). Moderate amounts of time exhibit increasing marginal utility (disutility) because larger blocks of time provide a more diverse set of usage opportunities. It is only when it is difficult to imagine how more (less) time would be beneficial (detrimental) that there is diminishing marginal utility (disutility) for time. Thus time valuation shows increasing marginal utility when there is a time deficit, but diminishing marginal utility when there is a time surplus. These findings have implications for how other resources might be valued.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA5My9qY3IvdWN2MDIx